N, P co-coordinated Fe species embedded in carbon hollow spheres for oxygen electrocatalysis. Issue 24 (5th June 2019) - Zhu, Xiaofeng; Tan, Xin; Wu, Kuang-Hsu; Chiang, Chao-Lung; Lin, Yu-Chang; Lin, Yan-Gu; Wang, Da-Wei; Smith, Sean; Lu, Xunyu; Amal, Rose
Abstract : Carbon hollow spheres (FeNPC) with single-atomic and octahedral FeN x P y active sites are fabricated for oxygen electrocatalysis. Abstract : The increasing interest in fuel cell technology and metal–air batteries has led to the need for stable and effective catalyst materials to replace noble metal (such as Pt) based benchmarks for the oxygen reduction reaction (ORR). In this study, carbon hollow spheres with highly dispersed nitrogen and phosphorus co-coordinated iron atoms (FeNPC) on their surface have been successfully fabricated, exhibiting exceptional ORR activity in both alkaline and acidic solutions. Specifically, the obtained FeNPC catalyst is capable of catalyzing the ORR with an onset potential of 1.03 V and a half-wave potential of 0.88 V (both vs. the reversible hydrogen electrode) in alkaline solution, outperforming the commercial Pt/C catalyst under identical conditions. Experimental results and theoretical simulations reveal that the quasi -octahedral O2 -FeN x P y species are the active sites of the FeNPC composite. These species modify the electronic configuration of Fe centers and weaken the adsorption of the OH* intermediate, thereby promoting the ORR process. Additionally, the FeNPC catalyst also displays a catalytic activity towards the anodic oxygen evolution reaction (OER), making it an active air electrode catalyst in rechargeable Zn–air batteries with a high peak power density of 233.2 mW cm −2 and an excellent cycling stability at 3 mA cm −2 for over 15 h.